2021
DOI: 10.1302/2046-3758.104.bjr-2020-0430.r1
|View full text |Cite
|
Sign up to set email alerts
|

Elution of rifampin and vancomycin from a weight-bearing silorane-based bone cement

Abstract: Aims Poly(methyl methacrylate) (PMMA)-based bone cements are the industry standard in orthopaedics. PMMA cement has inherent disadvantages, which has led to the development and evaluation of a novel silorane-based biomaterial (SBB) for use as an orthopaedic cement. In this study we test both elution and mechanical properties of both PMMA and SBB, with and without antibiotic loading. Methods For each cement (PMMA or SBB), three formulations were prepared (rifampin-added, vancomycin-added, and control) and made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…There are a few published studies that have reported carriers capable of RIF delivery for the treatment of bone infections. 18 , 22 - 24 In an in vitro study, Ahola et al 23 reported the potential of a β-tri-calcium phosphate-based material to deliver RIF or ciprofloxacin, but no combination studies were performed. In two separate studies, Qayoom et al 18 , 25 reported on a biphasic ceramic material as a carrier for RIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few published studies that have reported carriers capable of RIF delivery for the treatment of bone infections. 18 , 22 - 24 In an in vitro study, Ahola et al 23 reported the potential of a β-tri-calcium phosphate-based material to deliver RIF or ciprofloxacin, but no combination studies were performed. In two separate studies, Qayoom et al 18 , 25 reported on a biphasic ceramic material as a carrier for RIF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a silorane-based biomaterial made up of two silicon-containing oxiranes combined with SiO 3 fillers and Lamoreaux’s catalyst initiators was able to deliver RIF locally but lacked the biodegradable properties of the CaS/HA material. 22 In comparison to the materials used in these studies, the CaS/HA material used in the present study is a clinically proven and approved material, which potentially makes it easy for future clinical studies and clinical translation of CaS/HA as a carrier of RIF. One of the main indications for local delivery with an antibiotic containing CaS/HA is cavity filling of eradicated osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is a rat-based study, which cannot accurately represent human PJI and treatment conditions, as the absorption, distribution, metabolism, and excretion of drugs in rats differs from those in humans, 58 as well as the biodynamics and biomechanical characteristics of the knee. Second, although the available literature suggests that different debridement methods can influence PJI prognosis, 59 , 60 and some novel biomaterials can enhance the elution of vancomycin without attenuating the strength of cement, 61 our study aimed to compare the efficacy of different vancomycin administration approaches based on uniform debridement and vancomycin-loaded acrylic cement spacer implantation procedures. Third, our study compared the efficacy between vancomycin application approaches without the use of adjuvant oral antibiotics, such as rifampicin, which might affect the ability of the vancomycin spacer and/or systemic vancomycin treatment to eliminate the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these carriers cannot serve as appropriate spacers because of their biodegradable nature. Bone cement made of other undegradable materials, such as siloranebased biomaterial [61], may be a solution. Silorane-based cements were initially developed for the use in dentistry.…”
Section: Discussionmentioning
confidence: 99%